2019
DOI: 10.1073/pnas.1814545116
|View full text |Cite
|
Sign up to set email alerts
|

Cold sensing by Na V 1.8-positive and Na V 1.8-negative sensory neurons

Abstract: The ability to detect environmental cold serves as an important survival tool. The sodium channels NaV1.8 and NaV1.9, as well as the TRP channel Trpm8, have been shown to contribute to cold sensation in mice. Surprisingly, transcriptional profiling shows that NaV1.8/NaV1.9 and Trpm8 are expressed in nonoverlapping neuronal populations. Here we have used in vivo GCaMP3 imaging to identify cold-sensing populations of sensory neurons in live mice. We find that ∼80% of neurons responsive to cold down to 1 °C do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 35 publications
4
52
0
Order By: Relevance
“…27 In contrast, oxaliplatin did not affect thermal activation thresholds of basal cold-sensing neurons in vivo, when the hindpaw was stimulated with a range of temperature drops delivered by a Peltiercontrolled thermode ( Figure 1E). 20 Moreover, when we quantified peak fluorescence intensity in response to cold as a surrogate for excitability before and after oxaliplatin, cold-evoked fluorescence intensity in both the basal and silent populations in the oxaliplatin group was no different to vehicle ( Figure 1F). Collectively, these data indicate oxaliplatin does not markedly affect the activation thresholds or excitability of the basally-active cold-sensing neurons.…”
Section: Silent Cold-sensing Neurons Are Unmasked During Chemotherapymentioning
confidence: 95%
See 2 more Smart Citations
“…27 In contrast, oxaliplatin did not affect thermal activation thresholds of basal cold-sensing neurons in vivo, when the hindpaw was stimulated with a range of temperature drops delivered by a Peltiercontrolled thermode ( Figure 1E). 20 Moreover, when we quantified peak fluorescence intensity in response to cold as a surrogate for excitability before and after oxaliplatin, cold-evoked fluorescence intensity in both the basal and silent populations in the oxaliplatin group was no different to vehicle ( Figure 1F). Collectively, these data indicate oxaliplatin does not markedly affect the activation thresholds or excitability of the basally-active cold-sensing neurons.…”
Section: Silent Cold-sensing Neurons Are Unmasked During Chemotherapymentioning
confidence: 95%
“…In vehicle-treated mice, cold-sensing neurons were sparse and had small diameters, in agreement with earlier studies. 11,20,32 When we measured the size of neurons responding to either ice-water or acetone applied to the glabrous skin, cross-sectional areas were normally distributed and had a mean value of 214.9 µm 2 ( Figure 1C). In oxaliplatin-treated animals, small cells also responded to cold, however a novel, normally cold-insensitive population of large diameter neurons also became activated by cooling.…”
Section: Silent Cold-sensing Neurons Are Unmasked During Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, signs of positive selection were found in genes in the genome of R. tarandus mainly enriched in GO terms related to channel activity ( Supplementary Table S15), such as sodium channel activity and ion channel activity, which are thought to be relevant in cold sensing mechanisms 82 . The ability to detect and adapt to cold temperature is crucial for the survival of an organism 83,84 . The process of sensory transduction and a large array of ion channels, such as Na + and K + channels, are involved in cold temperature detection 82 .…”
Section: Discussionmentioning
confidence: 99%
“…While it is true that primary sensory neurons are capable of detecting and encoding environmental stimuli without accessory cells, our work suggests that proper somatosensation also requires critical stimulus amplification at the level of keratinocyte. Keratinocyte population activity (Koizumi et al, 2004) could also explain the extreme variability observed in DRG cold responses in vivo (Luiz et al, 2019); individual sensory neuron activity could be directly influenced by the non-neuronal cells in the local peripheral terminal environment. Before our work, global chemo (Pang et al, 2015)-and optogenetic (Baumbauer et al, 2015;Moehring et al, 2018) approaches had been used to illustrate the importance of keratinocyte-to-sensory neuron signaling in somatosensation.…”
Section: Purinergic Keratinocyte Signaling Is Also Required For Normamentioning
confidence: 99%